2020
DOI: 10.3233/bmr-171031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of electrotherapy in Bell’s palsy treatment: A systematic review

Abstract: BACKGROUND: Up to now there is not enough evidence that supports the use of electrotherapy in the treatment of Bell’s palsy. OBJECTIVE: Through a systematic review, we aimed to verify whether the use of electrotherapy is effective for treating Bell’s palsy or peripheral paralysis. METHODS: Publications were searched in PubMed, EBSCO and Web of Science. The present systematic review included studies that analyzed the electrotherapy as a therapeutic method for treating individuals with Bell’s palsy, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Our review has shown that an electrotherapy program can have a positive effect on BP symptoms. Burelo-Peregrino et al [19] agree with our findings as they concluded that electrotherapy helps improve symptoms in both acute and chronic BP. However, it is not clear what parameters (intensity, pulse duration, duration of treatment, Number of sessions) should be applied in order to obtain the best possible results.…”
Section: Discussionsupporting
confidence: 93%
“…Our review has shown that an electrotherapy program can have a positive effect on BP symptoms. Burelo-Peregrino et al [19] agree with our findings as they concluded that electrotherapy helps improve symptoms in both acute and chronic BP. However, it is not clear what parameters (intensity, pulse duration, duration of treatment, Number of sessions) should be applied in order to obtain the best possible results.…”
Section: Discussionsupporting
confidence: 93%
“…[5,6,[26][27][28] In the "complementary and alternative treatment" category, terms such as "acupuncture," "rehabilitation," "electroacupuncture," "physical therapy," and "low level laser therapy" were included. [29][30][31][32] Moreover, this category showed a tendency towards more recent studies, just as with "medication treatment". In other words, the research areas on the treatment of facial nerve palsy that are presently being focused on were "medication treatment" and "complementary and alternative treatment," indicating the probable direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…In dieser Studie war aber die Fallzahl mit insgesamt 87 Patienten gering [ 79 ]. In einer jüngst vorgelegten Metaanalyse zur Wirksamkeit der Elektrotherapie wurde kein Effekt für die Elektrotherapie allein nachgewiesen [ 10 ].…”
Section: Therapieunclassified